Role of astrocytes connexins - pannexins in acute brain injury - Juan E. Tichauer; Maximiliano Rovegno (Neurotherapeutics)
Acute brain injuries (ABIs) encompass a broad spectrum of primary injuries such as ischemia, hypoxia, trauma, and hemorrhage that converge into secondary injury where some mechanisms show common determinants. In this regard, astroglial connexin and pannexin channels have been shown to play an important role. These channels are transmembrane proteins sharing similar topology and form gateways between adjacent cells named gap junctions (GJs) and pores into unopposed membranes named hemichannels (HCs). In astrocytes, GJs and HCs enable intercellular communication and have active participation in normal brain physiological processes, such as calcium waves, synapsis modulation, regional blood flow regulation, and homeostatic control of the extracellular environment, among others. However, after acute brain injury, astrocytes can change their phenotype and modify the activity of both channels and hemichannels, which can result in the amplification of danger signals, increased mediators of inflammation, and neuronal death, contributing to the expansion of brain damage and neurological deterioration. This is known as secondary brain damage. In this review, we discussed the main biological mechanism of secondary brain damage with a particular focus on astroglial connexin and pannexin participation during acute brain injuries.